Delivering and evaluating a scalable training model for strengthening family medicine in resource-limited environments: the Gaza experience - Lovell,B; Dhillon,R; Khader,A; Seita,A; Al-Jadba,G; Kitamura,A; Rawaf,S; Newson,R (BJGP Open, 2019)
Background: Since 2007 Gaza Palestine has been subject to blockade affecting over 1.9 million people. This denies health professionals’ access to Continuing Professional Development (CPD). In Gaza, family physicians are scarce, and their level of training does not meet the needs of UNRWA’s Family Health Team model for better population health. Aim: This study sought to develop a postgraduate training programme for Gazan doctors via a Diploma in Family Medicine and evaluate its impact on physicians and patients.Design and setting: A mixed-methods evaluation of a postgraduate Diploma Methods: The programme was delivered over one year, to 15 primary care doctors. The impact was evaluated through focus group discussions and patient feedback questionnaire survey comparing FM PG Diploma graduate doctors and doctors without the FM PG Diploma. Results: All participating doctors graduated successfully and found the experience extremely positive. Trainees felt that the Diploma helped them take more individualised approach to patients; have a better understanding of psychosocial elements affecting patient health; feel more inclined towards team-working and collaborative approaches to healthcare; and more insight into non-verbal communication such as active listening and tactile gestures. Statistical analysis of patients feedback showed significantly improved patient-reported outcomes and satisfaction when treated by course diplomates compared to non-diplomates. Conclusion: Where there are limited training opportunities, investment in a structured Postgraduate Diploma training programme can improve quality of health service delivery. UNRWA’s experience in Gaza demonstrates the value of a scalable model in resource-limited settings.